(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Smart phones have become cheap and accessible to almost everyone in Pakistan. They are particularly quite common among students including medical students. However, question is still there whether medical students use these smart phones for study purpose also or it is just a way of communication. Objective: To determine the use of smart phones by 2nd year medical students of our college and to determine the usage of these phones for learning purposes. Material and Methods: This cross-sectional study was conducted at Avicenna Medical College. After the end of the lecture, all 2nd year students were given a proforma. The proforma determined the demographic details of the participants and the usage of devices, medical applications in the smart phones and their usage. Results: The mean age of the participants in this study was 20.02 ± 1.44 years. There were 69 females (72.6%) and 26 males (27.3%) in the study. Most of the participants (83.6%) owned a smart phone. All of the study participants told to use smart phones for sms, emails, internet and social media. Eighty five participants of 88 having smart phone (96.5%) were using it for educational purposes. When asked in detail, only 45 participants (51.1%) were having e-books in their smart phones. Sixty seven participants (70.5%) were having more than one medical application installed. Final question asked was the reason for not using mobile smart phone for educational and study purposes. The most commonly chosen option was paid applications and paid articles by 29 and 21 participants (30.5% and 22.1%) respectively. Also 6 participants (6.3%) labelled internet problems as cause for not using mobile smart phones for study purposes. Conclusion: It is concluded that most ofmedical students own smart phones, however their usage for learning and educational purposes is limited. So it is suggested that teachers must guide their students in this regard as usage of smart phones can be of great help in learning if properly used